Alcohol, Adipose Tissue and Lipid Dysregulation - Steiner, Jennifer L. (Biomolecules, 2017)
Chronic alcohol consumption perturbs lipid metabolism as it increases adipose tissue lipolysis and leads to ectopic fat deposition within the liver and the development of alcoholic fatty liver disease. In addition to the recognition of the role of adipose tissue derived fatty acids in liver steatosis, alcohol also impacts other functions of adipose tissue and lipid metabolism. Lipid balance in response to long-term alcohol intake favors adipose tissue loss and fatty acid efflux as lipolysis is upregulated and lipogenesis is either slightly decreased or unchanged. Study of the lipolytic and lipogenic pathways has identified several regulatory proteins modulated by alcohol that contribute to these effects. Glucose tolerance of adipose tissue is also impaired by chronic alcohol due to decreased glucose transporter-4 availability at the membrane. As an endocrine organ, white adipose tissue (WAT) releases several adipokines that are negatively modulated following chronic alcohol consumption including adiponectin, leptin, and resistin. When these effects are combined with the enhanced expression of inflammatory mediators that are induced by chronic alcohol, a pro-inflammatory state develops within WAT, contributing to the observed lipodystrophy. Lastly, while chronic alcohol intake may enhance thermogenesis of brown adipose tissue (BAT), definitive mechanistic evidence is currently lacking. Overall, both WAT and BAT depots are impacted by chronic alcohol intake and the resulting lipodystrophy contributes to fat accumulation in peripheral organs, thereby enhancing the pathological state accompanying chronic alcohol use disorder.